Hazards Mitigation of Lahar Flows on Semeru Volcano after the 4 December 2021 Eruption Based on PS-InSAR - Cholisina Anik Perwita; Faridha Aprilia; Sukir Maryanto; Harun Arrasyid; Aqyla Farah Tsabitah (TDMRC, Universitas Syiah Kuala, 2022)
Volcanic eruption is one of the phenomena that can change the volcanic landscape drastically. Monitoring of volcanic edifices after eruptions should be considered to further understand the potential hazards in the future. Satellite monitoring is a reliable technique for assessing deformation in a volcano. InSAR was applied to detect material build-up after the eruption phase of Semeru Volcano in December 2022. As a consequence of the opening crater along with the InSAR result, a lahar product after the eruption was deposited in the southwest direction. Significant deformations were indicated by PS-InSAR near the crater, which was characterized by a LOS displacement of -10 to -40 mm/year, indicating scouring of the pyroclastic material moving down the slope. The accumulation of pyroclastic flows from the abrading process below was detected in the proximal zone of Semeru, as shown by the positive LOS displacement ranging from 10 to 40 mm/year. The field survey conforms to the PS InSAR results, where unconsolidated material, ranging in size from gravel to boulders, piles up approximately 4-5 m in Curah Kobokan. Highly unconsolidated material tends to move easily by water and threaten the surrounding settlements. Overlying PS InSAR and drainage pattern in the flank of Semeru, concluding several locations that have a high-risk potential of being affected by lahar flows are Curah Kobokan, Supiturang Village, Pronojiwo District, then Tulungrejo, Pasropan Village, Pasrujambe District, Lumajang Regency.